Development of a two‐dimensional bipolar electrochemistry technique for high throughput corrosion screening - Yiqi Zhou; Dirk Lars Engelberg (Materials Genome Engineering Advances, 2024)
Abstract Bipolar electrochemistry allows testing and analysing the crevice corrosion, pitting corrosion, passivation, general corrosion, and cathodic deposition reactions on one sample after a single experiment. A novel two‐dimensional bipolar electrochemistry setup is designed using two orthogonal feeder electrode arrangements, allowing corrosion screening tests across a far wider potential range with a smooth potential gradient to be assessed. This two‐dimensional bipolar electrochemistry setup was applied here to simultaneously measure for the simultaneous measurement of the nucleation and propagation of pitting and crevice corrosion under a broad range of applied potential on type 420 stainless steel, which has a very short localised corrosion induction time. It reduces the error from corrosion induction to corrosion competition, and all pits and crevice corrosion have no lacy cover. Results show crevice corrosion can gain current density and easier to support its nucleation and propagation at different potential regions more easily than pitting corrosion.